Characterization of an Iterative Halogenase Acting on Ribosomal Peptides Underlies the Combinatorial Biosynthesis Logic of Lasso Peptides - Jin-Long Lu (11214882) (2025)
Halogenation is commonly utilized in medicinal chemistry for the improvement of drug leads. Flavin-dependent halogenases (FDHs) are ubiquitous across all domains of life, yet iterative FDHs are rare in the biosynthesis of ribosomally synthesized and post-translationally modified peptides (RiPPs). Herein, we characterize a novel iterative FDH, ChlH, which orchestrates nonsequential chlorination of two specific Trp within the core peptide of a lasso precursor containing three Trp. Biochemical and computational studies enable the characterization of ChlH, which employs unique protein-peptide interactions (PPIs) between its distinct N- and C-terminal motifs and a crucial recognition sequence (RS-II) downstream of RS-I in the leader peptide. Previous studies have demonstrated the indispensability of RS-I for lasso peptide biosynthesis, while RS-II was considered to be replaceable. Furthermore, we find that the core peptide substantially contributes to the PPI. Bioinformatic analysis reveals the prevalence of homologous FDHs in the biosynthetic gene clusters (BGCs) of various RiPP classes. Heterologous expression of the chl BGC yields non-, mono-, and dichlorinated lasso peptides, with chlorination, particularly dichlorination, enhancing their antibacterial activity. This study expands the FDH activity spectrum to include iterative catalysis on ribosomal peptides and underscores the significance of RS-II in tailoring enzymes for the combinatorial biosynthesis of lasso peptides.